2010
DOI: 10.1007/s00595-008-4055-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of right-sided diverticulitis: A retrospective review from a hospital in Japan

Abstract: Patients with acute right-sided diverticulitis seldom require emergency surgery unless acute appendicitis is misdiagnosed preoperatively. Most cases of uncomplicated right-sided diverticulitis, even if it is recurrent, can be treated conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
5
30
0
2
Order By: Relevance
“…Consequently, leftsided diverticulosis is more common in older patients. 25 in asians, diverticulitis occurs more frequently in the right colon, 26 a finding consistent with our results. in Western patients, however, diverticular disease usually affects the sigmoid and descending colon, with less frequent involvement of the cecum and ascending colon.…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, leftsided diverticulosis is more common in older patients. 25 in asians, diverticulitis occurs more frequently in the right colon, 26 a finding consistent with our results. in Western patients, however, diverticular disease usually affects the sigmoid and descending colon, with less frequent involvement of the cecum and ascending colon.…”
Section: Discussionsupporting
confidence: 94%
“…The recurrence rate after conservative management for right colonic uncomplicated diverticulitis varies among studies (approximately 7.1-20.5 %) [7,9,10]. The causes of recurrence are not yet understood.…”
Section: Introductionmentioning
confidence: 92%
“…1,2 In Japan, as in other Asian countries, more than half of the diverticulitis cases are right-sided. 3 No study has reported on the need for screening colonoscopy after diagnosing diverticulitis in Asian patients.…”
Section: To the Editormentioning
confidence: 99%